Atividade de novos antifúngicos sobre Candida spp. e Cryptococcus neoformans - Andrade, Claudia Sala (2004)
The fungal infections are becoming an important cause of morbidity and mortality in immunocompromised patients. Here we have studied the activity of new antifungal agents as ravuconazole, albaconazole, micafungin as well as fluconazole tpathogenic yeasts as Candida albicans, Candida dubliniensis, Candida tropicalis, Candida lusitaniae, Candida glabrata and Candida krusei. We have also included clinical and environmental isolates of Cryptococcus neoformans. The susceptibilities tests indicated that the majority of the strains were sensible to the antifungal agents studied but Candida albicans (6.6%) and C.tropicalis (3.3%) were classified as resistant to fluconazole. These results show the importance of monitoring of the susceptibility in yeast like fungi from clinical source and emphasize that new and constant susceptibility studies deserve be applied to Candida and Cryptococcus neoformans to reduce the mortality among immunocompromised patients.